Pelatihan Pengolahan Sampah untuk Peningkatan Ekonomi Kreatif Di Desa Kediren, Kecamatan Lembeyan, Kabupaten Magetan - Ahmad Fahrudin; Natsir, Ahmad (Madani: Jurnal Pengabdian Ilmiah, 2025)
This study aims to address the problem of plastic waste generated by children's activities at the Qur’anic Education Center (TPQ) in Kediren Village, Lembeyan Subdistrict, Magetan Regency, through community empowerment based on waste management. This is an applied research combined with community service activities. The method used is the Asset-Based Community Development (ABCD) approach, which focuses on developing local assets and potential. The results of this activity include the establishment of a waste bank in the village and improved community skills in transforming plastic waste into handicraft products such as decorative flowers, brooches, and wallets. This initiative has proven effective in reducing environmental pollution, increasing the economic value of plastic waste, and promoting the growth of the community's creative economy. Furthermore, this program represents a tangible contribution of higher education institutions in implementing the Tri Dharma of higher education, particularly in the aspect of community service.